Exercise and Arterial Stiffness in the Elderly: A Combined Cross-Sectional and Randomized Controlled Trial (EXAMIN AGE) - Arne Deiseroth; Lukas Streese; Sabrina Köchli; Romy Sandra Wüst; Denis Infanger; Arno Schmidt-Trucksäss; Henner Hanssen (Frontiers in Physiology, 2019)
Introduction:Arterial stiffness (AST) is a main determinant of cardiovascular (CV) mortality. Long-term physical activity (PA) is considered to decrease age-related progression of AST but effects of short-term exercise interventions on AST remain unclear.Methods:In a combined cross-sectional and interventional study approach, we investigated the effects of long-term PA and short-term high-intensity interval training (HIIT) on AST in an older population. 147 older individuals (mean age 59 ± 7 years) were assigned to three groups according to their PA and CV risk profile and compared: healthy active (HA, n = 35), healthy sedentary (HS, n = 33) and sedentary at risk (SR, n = 79). In addition, SR were randomized to either 12 weeks of HIIT or standard recommendations. Pulse wave velocity (PWV) was measured by applanation tonometry. Cardiorespiratory fitness (CRF) was performed by symptom-limited spiroergometry to determine maximal oxygen uptake (VO2max).Results:Higher CRF was associated with lower PWV (p < 0.001) and VO2max explained 18% of PWV variance. PWV was higher in SR (8.2 ± 1.4 m/s) compared to HS (7.5 ± 1.6 m/s) and HA (7.0 ± 1.1 m/s; p < 0.001). 12 weeks of HIIT did not change PWV in SR. HIIT-induced reduction in systolic BP was associated with a reduction in PWV (p < 0.05).Discussion:SR show higher PWV compared to HS and long-term PA is associated with lower PWV. Reduction of AST following short-term HIIT seems to depend on a concomitant decrease in blood pressure. Our study puts into perspective the effects of long- and short-term exercise on arterial wall integrity as treatment options for CV prevention in an older population.Clinical Trial Registration:ClinicalTrials.gov: NCT02796976 (https://clinicaltrials.gov/ct2/show/NCT02796976).